Efficacy of Homeopathic Medicine Ammi Visnaga Q in Cases of Non Segmental Vitiligo: A Single Blind Controlled Experimental Study. (Advancements in Homeopathic Research, 2025)
This study was aimed to evaluate the efficacy of Ammi Visnaga in mother tincture (Q) in the treatment of non-segmental vitiligo. A single blind, controlled experimental design was employed, involving 30 participants divided into two groups; 15 in the trial group and 15 in the control group. This study included 12 males and 18 females, aged 18 years and above. The trial group received Ammi Visnaga Q, while the control group was administered a placebo. The outcomes were measured using objective scales: VASI (Vitiligo Area Severity Index) to assess the severity of depigmentation, and VITILIGO LESION SEVERITY SCORE (VLSS) for overall lesion improvement and quality of life
Keywords: non-segmental; vitiligo; depigmentation; VITILIGO LESION SEVERITY SCORE